Locating the freeze-out curve in heavy-ion collisions - Bluhm, Marcus; Nahrgang, Marlene; Pawlowski, Jan M. (Arxiv, 2020)
Based on transport equations we argue that the chiral dynamics in heavy-ion collisions at high collision energies effectively decouples from the thermal physics of the fireball. With full decoupling at LHC energies the chiral condensate relaxes to its vacuum expectation value on a much shorter time scale than the typical evolution time of the fluid dynamical fields and their fluctuations. In particular, the net-baryon density remains coupled to the bulk evolution at all collision energies. As the mass scales of the hadrons are controlled by the chiral condensate, it is reasonable to employ vacuum masses in the statistical description of the hadron production at the chemical freeze-out for high collision energies. We predict that at lower collision energies the coupling of the chiral condensate to the thermal medium gradually increases with consequences for the related hadronic masses. A new estimate for the location of the freeze-out curve takes these effects into account.
Gesehen am 07.10.2022